Bacterial communities within Phengaris (Maculinea) alcon caterpillars are shifted following transition from solitary living to social parasitism of Myrmica ant colonies. Issue 8 (2nd April 2019) - Szenteczki, Mark A.; Pitteloud, Camille; Casacci, Luca P.; Kešnerová, Lucie; Whitaker, Melissa R.L.; Engel, Philipp; Vila, Roger; Alvarez, Nadir
Abstract: Bacterial symbionts are known to facilitate a wide range of physiological processes and ecological interactions for their hosts. In spite of this, caterpillars with highly diverse life histories appear to lack resident microbiota. Gut physiology, endogenous digestive enzymes, and limited social interactions may contribute to this pattern, but the consequences of shifts in social activity and diet on caterpillar microbiota are largely unknown. Phengaris alcon caterpillars undergo particularly dramatic social and dietary shifts when they parasitize Myrmica ant colonies, rapidly transitioning from solitary herbivory to ant tending (i.e., receiving protein‐rich regurgitations through trophallaxis). This unique life history provides a model for studying interactions between social living, diet, and caterpillar microbiota. Here, we characterized and compared bacterial communities within P .  alcon caterpillars before and after their association with ants, using 16S rRNA amplicon sequencing and quantitative PCR. After being adopted by ants, bacterial communities within P. alcon caterpillars shifted substantially, with a significant increase in alpha diversity and greater consistency in bacterial community composition in terms of beta dissimilarity. We also characterized the bacterial communities within their host ants ( Myrmica schencki ), food plant ( Gentiana cruciata ), and soil from ant nest chambers. These data indicated that the aforementioned patterns were influenced by bacteria derived from caterpillars' surrounding environments, rather than through transfers from ants. Thus, while bacterial communities are substantially reorganized over the life cycle of P. alcon caterpillars, it appears that they do not rely on transfers of bacteria from host ants to complete their development. Abstract : We characterized and compared the bacterial communities within Phengaris (Maculinea) alcon caterpillars, before and after their shift from herbivory to social parasitism of Myrmica ant colonies. We observed substantial shifts in the structure and diversity of bacterial communities after P. alcon caterpillars were adopted by ants. However, environmentally derived bacteria likely contributed to these patterns. Ultimately, it appears that P. alcon caterpillars do not rely on transfers of bacteria from host ants across their remarkable life cycle.